Analysis of the Implementation of MSME Financing Development at PT. Bank Sumut KCP Sy Hamparan Perak - Nuraini Najwa; Riswan Rambe (AHKAM, 2025)
This study analyzes the implementation of MSME financing development at PT Bank Sumut KCPsy Hamparan Perak, with a focus on strategies, challenges, and solutions within the framework of Islamic banking. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation, and analyzed using data reduction, presentation, and conclusion techniques. The findings reveal that MSME financing is implemented comprehensively by prioritizing sharia principles, including direct engagement with business actors, financing through mudharabah and musyarakah contracts, and provision of post-financing assistance. However, several obstacles hinder optimal implementation, such as low financial literacy, limited business legality, unstable MSME income, and insufficient field officers. To address these challenges, the bank has introduced financial literacy programs, assisted with business legality, enhanced officer capacity, and developed digital innovations. These measures have contributed to sustaining growth in financing while reinforcing the role of Islamic banks in supporting community-based economic development.